Digital Libraries: Technology and Management of Indigenous Knowledge for Global Access - Sembok, Tengku Mohd. T. (Springer, 2012)
This book constitutes the refereed proceedings of the 6th International Conference on Asian Digital Libraries, ICADL 2003, held in Kuala Lumpur, Malaysia in December 2003.